RI 7112 Chromium By Thermal Decomposition Of Bisbenzene Chromium - B. D. Nash (The National Institute for Occupational Safety and Health (NIOSH), 1968)
The object of this research was to investigate the technical feasibility of preparing chromium metal by the thermal decomposition of bisbenzene chromium. Bisbenzene chromium, a pi-bonded sandwich type organometallic compound, was thermally decomposed under reduced pressure to form a metal plate on a heated substrate. Metal recovery was close to 100 percent of theoretical, with deposition rates up to 20.8 mg/hr/cm2. Metal purity was dependent not only upon the purity of the starting material, but also upon the sublimation rate of bisbenzene chromium. Total detectable metallic impurities ranged from a low of 18 ppm to several hundred ppm. In general, metallic impurities were less than 100 ppm. Carbon, the major nonmetallic impurity, ranged from less than 0.3 percent to more than 10 percent. The carbon contamination is most likely a result of the decomposition of the organic portion of bisbenzene chromium. An unusual property of some of the deposits was their outstanding corrosion resistance. Unlike pure electrolytic chromium, which dissolves readily, these deposits were insoluble in hot mineral acids.